Pencapaian Keterampilan Meneliti Abad Ke-21 Peserta Didik SMA pada Pembelajaran Ekosistem melalui Step-By-Step Model Experiment - Roito, Erlien; Solihat, Rini; Wulan, Ana Ratna (Assimilation: Indonesian Journal of Biology Education, 2019)
Research skills achievement for 21st century learner in ecosystem concept through step-by-step model experiment were described in this research. Participant were 32 senior high school students which in the tenth grade. Research skills in this study are defined as the skill for finding sources of information, formulating problem, hypothesizing, analyzing data, evaluating data, and communicating in writing skill. Data was collected from student worksheets, research report, questionnaires, interviews, and field notes. Data collected were analyzed by identifying the student’s answer with RSD rubric category, then student’s score was processed into percentage in the form of table. The result showed that almost half of the students had fulfilled the criteria of maximal skill in finding the relevant source and analyzing data aspect, almost all students had fulfilled the criteria of maximal skill in formulating the problem and hypothetical aspect, most of the students had fulfilled the maximal skill criteria on evaluating data aspect, and a few of the students had fulfilled the maximal skill criteria on communicating aspect. Based on data analysis, it is found that the student achievement diverse on every aspect of research skills.